INTEREST AND THE TRUTH-IN-LENDING BILL. - Botts, Ralph R. (The Accounting Review, 1963)
The article presents information on the Truth-in-Lending Bill. This bill would have required merchants to post on each article offered for sale on time, the simple annual interest rate at which the time price is figured, along with related information such as the cash price, the downpayment and the finance or interest charge in dollars. Similarly, a money lender would have been required to disclose the simple annual interest rate at which a loan is offered, as well as the interest charge in dollars. The first step would be to include instructions, covering an equal-installment time transaction. A second step would be to give credit vendors a set of alternative instructions on how the equivalent annual interest rate might be computed directly from the amount to be financed or beginning balance (cash price minus downpayment) without computing an average balance. All time merchants would not be expected to understand the arithmetic involved in the alternative method. A third step might be to include in the bill a table from which credit vendors could find the equivalent annual interest rate for an equal monthly installment transaction after the finance.